2014
DOI: 10.1038/tp.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial respiration in peripheral blood mononuclear cells correlates with depressive subsymptoms and severity of major depression

Abstract: Mitochondrial dysfunction might have a central role in the pathophysiology of depression. Phenotypically, depression is characterized by lack of energy, concentration problems and fatigue. These symptoms might be partially explained by reduced availability of adenosine triphosphate (ATP) as a consequence of impaired mitochondrial functioning. This study investigated mitochondrial respiration in peripheral blood mononuclear cells (PBMCs), an established model to investigate the pathophysiology of depression. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(177 citation statements)
references
References 56 publications
12
158
1
6
Order By: Relevance
“…On the other hand, respiratory rates were unchanged in permeabilized platelets of MDD patients. Karabatsiakis et al (2014) also confirmed that mitochondrial respiration of PBMCs is significantly decreased in MDD patients. Importantly, decline of respiratory activity is negatively correlated with the severity of depressive symptoms, such as loss of energy, difficulties concentrating and fatigue etc.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…On the other hand, respiratory rates were unchanged in permeabilized platelets of MDD patients. Karabatsiakis et al (2014) also confirmed that mitochondrial respiration of PBMCs is significantly decreased in MDD patients. Importantly, decline of respiratory activity is negatively correlated with the severity of depressive symptoms, such as loss of energy, difficulties concentrating and fatigue etc.…”
Section: Introductionsupporting
confidence: 66%
“…They also showed a significant decrease of mitochondrial ATP production rates and mitochondrial enzyme ratios in the MDD muscles compared to controls. Two other groups investigated mitochondrial respiration via high-resolution respirometry in the intact and permeabilized platelets of MDD patients and found significant decrease of respiration efficiency in intact platelets in this population (Hroudová et al 2013; Karabatsiakis et al 2014). On the other hand, respiratory rates were unchanged in permeabilized platelets of MDD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last fifteen years, research has identified physiological changes associated with depressive disorders that are consistent with increased biological aging (defined as systemic aging beyond that which is expected for one’s chronological age). 29–32 The proliferation of mitochondrial DNA damage or dysfunction, mitochondrial dysfunction associated with oxidative stress both in the brain and the periphery, and increased proinflammatory cytokines such as tumor necrosis factor alpha (TNFα) or Interleukin 6 (IL6) are associated with a cycle resulting in cellular senescence and apoptosis, 33 major depression and other psychiatric illnesses, 34,35 and decreased physical activities, slowing and mobility deficits, and decrements in energy capacity in older adults. 3639 Furthermore, depression in late life is associated with greater decrements in physical functioning.…”
Section: Biological Substrates Of the Depressed Frail Phenotypementioning
confidence: 99%
“…These clinical symptoms may be partly attributed to reduced synthesis of adenosine triphosphate (ATP) due to mitochondrial dysfunction [41][42][43]. ATP, which is produced by mitochondria, is the main source of cellular energy.…”
Section: Lllt Enhances Atp Biosynthesismentioning
confidence: 99%